1993
DOI: 10.1007/bf03348878
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glucagon receptors in human adipocytes from a liposarcoma

Abstract: The presence of glucagon receptors on human adipocytes has not yet been described. In this work we present an exceptional case of glucagon binding to human adipocytes taken from a malignant tumor of adipose tissue of a patient with a liposarcoma. Binding analysis revealed that the total number of glucagon receptors on liposarcoma-cells was 99,000 and the apparent receptor affinity (ED:50) was 5 x 10(-9) M. Despite the presence of these specific receptors, glucagon was unable to induce a lipolytic response, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Specific antibodies directed against the glucagon receptor are necessary in addressing this question, but development of specific antibodies against glucagon receptors has been challenging and the antibodies available are unspecific and therefore not suitable for receptor localization (van der Woning et al, 2016). As an example, one study reported localization of the glucagon receptor in rat adipocytes using a monoclonal antibody (Iwanij and Vincent, 1990) whereas another using autoradiography, glucagon receptors were not found to be expressed (Watanabe et al, 1998), and no studies have demonstrated presence of glucagon receptors on human adipocytes (Carranza et al, 1993). Clearly, future studies should investigate glucagon receptor expression using antibody and antibody-independent methods.…”
Section: Glucagon Might Stimulate Lipolysis In Adipose Tissue In Rodementioning
confidence: 99%
“…Specific antibodies directed against the glucagon receptor are necessary in addressing this question, but development of specific antibodies against glucagon receptors has been challenging and the antibodies available are unspecific and therefore not suitable for receptor localization (van der Woning et al, 2016). As an example, one study reported localization of the glucagon receptor in rat adipocytes using a monoclonal antibody (Iwanij and Vincent, 1990) whereas another using autoradiography, glucagon receptors were not found to be expressed (Watanabe et al, 1998), and no studies have demonstrated presence of glucagon receptors on human adipocytes (Carranza et al, 1993). Clearly, future studies should investigate glucagon receptor expression using antibody and antibody-independent methods.…”
Section: Glucagon Might Stimulate Lipolysis In Adipose Tissue In Rodementioning
confidence: 99%
“… 58 The binding of glucagon to its membrane receptor initiates a signaling cascade, involving G proteins and adenylate cyclase that culminates in the increase of intracellular cAMP levels, subsequently activating protein kinase A (PKA) that phosphorylates further downstream effectors. 59 Even though the glucagon receptor was found expressed in adipocytes from rat 60 and human liposarcoma, 61 physiological levels of glucagon did not show an effect on lipolysis in murine WAT. 62 Thus, hepatic glucagon signaling is relying on phosphorylation to mediate fed-state appropriate blood glucose levels, only with peripheral mechanisms acting in adipocytes.…”
Section: Discussionmentioning
confidence: 95%
“…Receptors for glucagon and physiologic incretins (e.g., GIP) are present on adipocytes in animals, but it is not clear if they are also present on human adipocytes; these receptors may play a role in fat metabolism, with GIP promoting lipolysis (51)(52)(53)(54)(55)(56). These receptors are downregulated in certain animal models of T2D.…”
Section: Incretins In Physiologic Perspectivementioning
confidence: 99%